Icon, Daoist - Gesterkamp, Lennert (2021)
Images of Daoist deities first appeared at the end of the Han dynasty. Nevertheless, many of the same cosmological principles that govern Daoist icons, such as their iconography and spatial arrangement, have antecedents in pre-Han times, and were incorporated in later Daoism. Laozi (sixth century bce) is the spiritual founder of Daoism and, after his deification in the Han period, his images are among the first Daoist icons made. In the following centuries, the number of deities was greatly expanded, constituting a celestial bureaucracy governing all realms of the universe from its cosmic axis, Mount Kunlun, and later Jade Capital Mountain, where all the deities convened in an audience at the Heavenly Court. According to Daoist texts the Dao is formless and its deities are hypostases of the cosmic forces in anthropomorphic disguise. In Daoist rituals, a microcosmos is recreated during which the deities are visualized. The icons are the visual aids for these rituals, and their production ensures the accumulation of merit. Their iconography is not based on the visualization, but on pictorial models and cosmological principles such as number, color, and direction. From the beginning, there was a strong interaction with Buddhist art. Contrary to Buddhist and popular icons, however, no magical powers or deity presence are ascribed to the icons in the official Daoist understanding, but such views may have varied by period and audience. <br